The anticancer activity of bile acids in drug discovery and development - Li, Weijian; Zou, Lu; Huang, Shuai; Miao, Huijie; Liu, Ke; Geng, Yajun; Liu, Yingbin; Wu, Wenguang (Frontiers in Pharmacology, 2024)
Bile acids (BAs) constitute essential components of cholesterol metabolites that are synthesized in the liver, stored in the gallbladder, and excreted into the intestine through the biliary system. They play a crucial role in nutrient absorption, lipid and glucose regulation, and the maintenance of metabolic homeostasis. In additional, BAs have demonstrated the ability to attenuate disease progression such as diabetes, metabolic disorders, heart disease, and respiratory ailments. Intriguingly, recent research has offered exciting evidence to unveil their potential antitumor properties against various cancer cell types including tamoxifen-resistant breast cancer, oral squamous cell carcinoma, cholangiocarcinoma, gastric cancer, colon cancer, hepatocellular carcinoma, prostate cancer, gallbladder cancer, neuroblastoma, and others. Up to date, multiple laboratories have synthesized novel BA derivatives to develop potential drug candidates. These derivatives have exhibited the capacity to induce cell death in individual cancer cell types and display promising anti-tumor activities. This review extensively elucidates the anticancer activity of natural BAs and synthetic derivatives in cancer cells, their associated signaling pathways, and therapeutic strategies. Understanding of BAs and their derivatives activities and action mechanisms will evidently assist anticancer drug discovery and devise novel treatment.